Using the KBM App to Improve Teacher Writing Skills - Ilmatus Sa’diyah; Abdul Hamid; Widi Wurjani; Alita Pratitisyaning Darwanto; Aprilia Devi Nur Aini; Rahmat Noval Herlambang (Nusantara Science and Technology Proceedings, 2022)
The teacher's writing ability is still low. This is triggered by the condition of the teachers who do not have sufficient insight about writing and are not used to doing research. If teachers do not have good writing and reading skills, of course, the literacy level in schools cannot be expected to grow optimally. The reason is, teachers are the foundation in building literacy in schools. Therefore, teachers need to be given space to be skilled at writing. The method used is structured writing training using the KBM App application. This application makes it easy for teachers to write because teachers only need to use a smartphone/mobile phone to write. On the sidelines of time, teachers can write while lying down at home even once. The writing training activity lasted for a day with two broad materials, namely material for using the KBM App application, training in writing popular articles, and writing training with the KBM App application. From this training, teachers have increased their knowledge and skills in writing.